2006
DOI: 10.1176/appi.psy.47.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Somatic Symptoms With the CES–D to Assess Depression in Cancer Patients After Treatment: Comparison Among Patients With Oral/Oropharyngeal, Gynecological, Colorectal, and Breast Cancer

Abstract: Measuring somatic symptoms with the CES-D to assess depression in cancer patients after treatment van Wilgen, C.P.; Dijkstra, P.U.; Stewart, R.E.; Ranchor, A.V.; Roodenburg, J.L.N. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…33 Women in our control group reported a mean CES-D score of 10.10, resembling breast cancer survivors from that study, while the mean CES-D score in the CBSM group ( M =4.69) was significantly lower than scores among healthy controls [ t (276)=3.47, p =.001] and breast cancer survivors [ t (242)=4.52, p <.0001].…”
Section: Discussionmentioning
confidence: 51%
“…33 Women in our control group reported a mean CES-D score of 10.10, resembling breast cancer survivors from that study, while the mean CES-D score in the CBSM group ( M =4.69) was significantly lower than scores among healthy controls [ t (276)=3.47, p =.001] and breast cancer survivors [ t (242)=4.52, p <.0001].…”
Section: Discussionmentioning
confidence: 51%
“…Breast cancer patients that are recruited through the use of Internet-support group sites (Lieberman & Goldstein, 2005) have reported higher amounts of depressive symptoms than the current sample and work by Van Wilgen et al (2006). In Lieberman and Goldstein's (2005) study over 58% of the sample scored a 16 or higher on their total depression score.…”
Section: Limitationsmentioning
confidence: 64%
“…Our results compare favorably to Van Wilgen, Dukstra, Stewart, Ranchor, and Roodenburg (2006), whose sample showed a 22% prevalence of depressive symptoms. The current breast cancer sample was compared to a sample of 189 breast cancer patients (Van Wilgen et al, 2006), with mean and standard deviation for the total depression score of 10.5 (SD ¼ 8.30). The same procedure as described above was used (Welkowitz et al, 1982), and the results showed that there was no significant difference between the two samples on the mean total depression score, t(238) ¼ 1.26, p 0.10.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of psychological distress is complicated by the fact that patients may have had a preexisting mental health problem [16]. A number of studies have reported on cross-sectional and longitudinal incidence of anxiety and depression in patients with head and neck cancer [17]. The extent of depression that results from the experience of cancer itself is believed to be relatively low [18], which has encouraged these authors to call for a screening instrument to pick depressive symptoms pretreatment.…”
Section: Assessment Of Psychological Distressmentioning
confidence: 99%